Soils For Health: Enhancing Human Nutrition from the Ground Up - Welch, Ross M. (2010)
IFPRI 2020 Panel Discussion "Nourishing Plants and People New Insights on How Fertilizers Affect Agriculture Nutrition, & Health" by Dr. Welch